2020
DOI: 10.1364/jocn.391803
|View full text |Cite
|
Sign up to set email alerts
|

Analog fiber-wireless downlink transmission of IFoF/mmWave over in-field deployed legacy PON infrastructure for 5G fronthauling

Abstract: We present a fixed mobile convergence topology for analog intermediate frequency over fiber (A-IFoF)/millimeter-wave (mmWave) transmission, benefiting from the reuse of the deployed passive optical network (PON) infrastructure, towards future mobile fronthaul architectures. Powerful fully programmable gate array boards located inside the access nodes convert the Ethernet-based traffic to orthogonal frequency-division multiplexing (OFDM)-modulated intermediate frequency (IF) waveforms, supporting the A-IFoF pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The real-time IFoF mmW link applied in the HTS experiment has achieved a data rate of 1.5 Gbps [9]. A 1.6 Gbps orthogonal frequency-division multiplexing (OFDM) modulation outdoor transmission is successfully real-time transmitted by an applied analog-IFoF link [10]. The IFoF-based distributed antenna system (DAS) with 2 × 2 MIMO achieved 2 Gbps transmission in the indoor scenario [11], the same setup with 4×4 MIMO successfully transmitted around 9 Gbps into the IFoF-based mobile fronthaul [12].…”
Section: Conclusion and Discssionmentioning
confidence: 99%
“…The real-time IFoF mmW link applied in the HTS experiment has achieved a data rate of 1.5 Gbps [9]. A 1.6 Gbps orthogonal frequency-division multiplexing (OFDM) modulation outdoor transmission is successfully real-time transmitted by an applied analog-IFoF link [10]. The IFoF-based distributed antenna system (DAS) with 2 × 2 MIMO achieved 2 Gbps transmission in the indoor scenario [11], the same setup with 4×4 MIMO successfully transmitted around 9 Gbps into the IFoF-based mobile fronthaul [12].…”
Section: Conclusion and Discssionmentioning
confidence: 99%
“…FiWi mm-wave/IFoF architectures, which include digital or analog RoF approaches followed by wireless transmission, have benefited from diverse technical solutions aimed at improving capacity and coverage [30][31][32]. For instance, Li et al reported a 24 Gbit/s FiWi mm-wave link by exploiting 6 GHz bandwidth [30], whereas Argyris et al demonstrated a similar bit rate in a mm-wave/IFoF link with electrical subcarrier multiplexing [31].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…For instance, Li et al reported a 24 Gbit/s FiWi mm-wave link by exploiting 6 GHz bandwidth [30], whereas Argyris et al demonstrated a similar bit rate in a mm-wave/IFoF link with electrical subcarrier multiplexing [31]. Mm-wave/IFoF links have even been deployed over legacy PON as an alternative for 5G fronthauling [32].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…This is supported through a widespread deployment of remote radio heads (RRH), which shall be accompanied by a high degree of simplification of this field-distributed hardware at the antenna site [1]. In view of cloud-based radio networks with centralized baseband processing, as it is supported through antenna remoting by means of analogue radio-over-fiber transmission [2][3][4][5], this calls for improvements with respect to the opto-electronic RRH interface on the one hand, and transparent radio frequency (RF) electronics on the other hand. Up to now, most Manuscript received May 31, 2022.…”
Section: Introductionmentioning
confidence: 99%